Distributed ice thickness and volume of all glaciers around the globe - Huss, Matthias; Farinotti, Daniel (Journal of Geophysical Research: Earth Surface, 2012)
A new physically based approach for calculating glacier ice thickness distribution and volume is presented and applied to all glaciers and ice caps worldwide. Combining glacier outlines of the globally complete Randolph Glacier Inventory with terrain elevation models (Shuttle Radar Topography Mission/Advanced Spaceborne Thermal Emission and Reflection Radiometer), we use a simple dynamic model to obtain spatially distributed thickness of individual glaciers by inverting their surface topography. Results are validated against a comprehensive set of thickness observations for 300 glaciers from most glacierized regions of the world. For all mountain glaciers and ice caps outside of the Antarctic and Greenland ice sheets we find a total ice volume of 170 × 103 ± 21 × 103 km3, or 0.43 ± 0.06 m of potential sea level rise. Key Points First ice volume assessment of all individual glaciers around the globe Novel methodology to estimate glacier ice thickness distribution Potential sea level rise of 170,000 glaciers and ice caps worldwide is 0.43 m